Trade Policy along the Global Value Chain: A Rationale for the Existence of Deep Trade Agreements - Hartmut Egger; Christian Fischer-Thöne (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper sets up a model of trade, in which two countries with differing levels of technology specialize in the production of sub-stages of the global value chain. In the open economy, the technologically backward country exports intermediates in exchange for imports of a homogeneous consumption good from the technologically advanced country. This vertical specialization gives the two countries access to different policy instruments for appropriating rents in the open economy. The technologically advanced country can impose an import tariff on intermediates to lower foreign wages and increase national welfare. An import tariff is ineffective for the technologically backward economy, which can instead lower institutional quality and allow its workers to consume intermediate goods at a utility discount. In a non-cooperative policy equilibrium, the incentives to appropriate rents can be strong enough to lower welfare of the two countries to their autarky levels. This gives scope for a deep trade agreement that conditions tariff reductions on institutional quality improvements and is beneficial for both countries. Empirical evidence shows support for the main mechanisms of the model.
Keywords: F12; F13; F68; 330; global value chains; trade policy; institutional quality; tariffs; deep trade agreements